2014
DOI: 10.1002/jor.22660
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous cannabinoid anandamide impairs cell growth and induces apoptosis in chondrocytes

Abstract: Endocannabinoids has been described to be involved in articular degenerative disease by modulating nociception and immune system. However, the role of the endocannabinoid anandamide on chondrocyte cell viability is still unclear. Therefore, we decided to study anandamide's effects on chondrocytes viability and to evaluate its interactions with the catabolic factor TNF (tumor necrosis factor). Chondrocyte vitality was evaluated by MTT assay. We investigated LDH release, chromatin condensation, cleavage of focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Recent evidences suggested that activated AMPK was involved in the anti-apoptotic effect on potential chondroprotection [41,42], and chondrocyte apoptosis was accompanied by increased phosphorylation of p38 MAPK Fig. 8 a Immunohistochemical analyses of caspase-3, Bax, Bcl-2, and Col II expressions in each group (original magnification 9200 and zoom-in areas magnification 9400).…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidences suggested that activated AMPK was involved in the anti-apoptotic effect on potential chondroprotection [41,42], and chondrocyte apoptosis was accompanied by increased phosphorylation of p38 MAPK Fig. 8 a Immunohistochemical analyses of caspase-3, Bax, Bcl-2, and Col II expressions in each group (original magnification 9200 and zoom-in areas magnification 9400).…”
Section: Discussionmentioning
confidence: 98%
“…AEA has been found to decrease chondrocyte vitality, although this effect was not CB receptor‐dependent. Nevertheless, it was also shown to work in synergy with TNFα to cleave caspase‐3 and induce apoptosis, thus facilitating cartilage degeneration (Gómez et al ., ). Therefore, it is important to further identify the role of these receptors within normal and OA cartilage to clarify their role in healthy tissue and their potential as possible targets in the treatment of OA (Dunn et al ., ).…”
Section: Effects Of Cannabinoids On Osteoarthritic Cartilagementioning
confidence: 99%
“…To date a detailed analysis of endocannabinoid levels in OA patients and their influence upon OA-associated pain has not been reported despite the well-documented role of endocannabinoids in the modulation of pain and the recognized presence of cannabinoid receptors on chondrocytes [14]. A single clinical study has examined endocannabinoid levels in the synovial fluid of OA patients and found elevated AEA and 2-AG levels and reduced content of the anti-inflammatory PEA [45], possibly reflecting a pro-inflammatory and proalgesic environment.…”
Section: Introductionmentioning
confidence: 99%